REHABILITATION OF PHYSICAL DECONDITION SYNDROME POST –COVID19 TO SECOND AGE MEN WITH EXOGENOUS OBESITY - Pogorlețchi Ala; Mihailov Natalia (Sport şi Societate)
The global rise in overweight and obesity has become a significant health issue, particularly highlighted during the COVID-19 pandemic. Obesity not only increases the risk of severe disease and complications from SARS-CoV-2 but also exacerbates symptoms of post-COVID syndrome. This complex of symptoms is often more pronounced in individuals with obesity, leading to greater challenges in recovery.The article discusses the implementation of a rehabilitation program specifically designed for obese patients recovering from COVID-19, focusing on addressing physical deconditioning. The program aims to improve overall health outcomes by enhancing physical fitness and alleviating post-COVID symptoms. By tailoring rehabilitation strategies to meet the unique needs of this population, the initiative seeks to promote better recovery trajectories and improve quality of life for those affected